Seafloor Crustal Deformation on Ocean Bottom Pressure Records With Nontidal Variability Corrections: Application to Hikurangi Margin, New Zealand. Issue 1 (13th January 2019) - Muramoto, Tomoya; Ito, Yoshihiro; Inazu, Daisuke; Wallace, Laura M.; Hino, Ryota; Suzuki, Syuichi; Webb, Spahr C.; Henrys, Stuart
Abstract: Ocean bottom pressure (OBP) observations are a powerful tool for determining vertical crustal displacements, especially due to earthquakes and slow earthquakes, with centimeter‐level resolution. In these studies, removal of oceanographic noise (tens of centimeters) is required to identify centimeter‐level crustal deformation. We undertake barotropic modeling to remove oceanographic signals from data from an OBP array deployed offshore New Zealand in 2014/2015. We show that removing the nontidal component calculated from a barotropic ocean model reduces the variance in the data by about 66% and provides a feasible means to resolve pressure changes due to crustal deformation during the slow slip events. We also discuss the vertical displacements from slow slip events that occurred in late September to mid‐October 2014, and we outline our procedure for processing OBP data. Plain Language Summary: We developed a new method for determining pressure changes due to slow slip events (SSEs) on offshore subduction plate boundaries by using information from the ocean bottom pressure records and numerical simulation. We use an oceanographic model to correct the seafloor pressure data for oceanographic signals, so that centimeter‐level vertical deformation of the seafloor during the SSEs can be isolated. We show that this method can be used to identify SSEs that occurred off the coast of New Zealand in 2014. Our results indicate that our ocean model can be a useful tool to use ocean bottom absolute pressure gauge data to resolve crustal deformation. Key Points: The oceanographic corrections from our model help to reduce noise in ocean bottom pressure data recorded during slow slip event We show a barotropic oceanographic model can be used to reduce the variance in seafloor pressure measurements by about 66% Our oceanographic model is particularly valuable for the shallower‐water sites